“The Gaps in History Need to be Closed and, Above All, Described”: Hungarian Literature on the Holocaust between 1944–1948 - Karolak, Sylwia (Porównania, 2021)
The author discusses Kinga Piotrowiak-Junkiert’s book From Idyll to Irony. Hungarian Literature on the Holocaust between 1944–1948 (Adam Mickiewicz University Press, Poznan 2020).